Biological and haematological safety profile of oral amodiaquine and chloroquine in healthy volunteers with or without Plasmodium falciparum infection in northeast Tanzania - Massaga, JJ; Lusingu, JP; Makunde, R; Malebo, HM; Chile, MM; Akida, JA; Lemnge, MM; Rønn, AM; Theander, TG; Bygbjerg, IC; Kitua, AY (Tanzania Journal of Health Research, 2008)
Amodiaquine (AQ), an effective antimalarial drug for uncomplicated malaria, has been greatly restricted after cases of life-threatening agranulocytosis and hepatic toxicity during prophylactic use. We conducted a hospital based open-label randomised clinical trial in 40 indigenous semi-immune healthy adult male volunteers with and without malaria parasites. The objective was to collect data on biological and haematological safety, tolerability, and parasitological efficacy to serve as baseline in the evaluation of the effectiveness of AQ preventive intermittent treatment against malaria morbidity in infants. Volunteers were stratified according to parasitaemia status and randomly assigned 20 participants each arm to three days treatment with either AQ or chloroquine (CQ). The levelof difference of selected haematological and hepatological values pre-and post-trial were marginal and within the normal limits. Clinical adverse effects mostly mild and transient were noticed in 33.3% CQ treated-aparasitaemic, 23.8% of CQ treated-parasitaemic, 28.6% of AQ-treated parasitaemic and 14.3% of aparasitaemic receiving AQ. Amodiaquine attained 100% parasitological clearance rate versus 70% in CQ-treated volunteers. The findingsindicate that there was no agranulocytosis or hepatic toxicity suggesting that AQ may pose no public health risk in its wide therapeutic dosage uses. Larger studies are needed to exclude rare adverse effects Keywords: Amodiaquine, chloroquine, biological, haematological, safety, treatment, malaria, Tanzania Tanzania Journal of Health Research Vol. 10 (3) 2008: pp. 144-150